CODE MIXING USED IN WHATSAPP ACADEMIC GROUPS CHATS IN ENGLISH LITERATURE IN 2018 AT UNIVERSITAS NEGERI MAKASSAR - Nuryanti, Risna; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
Code Mixing in WhatsApp academic groups Chats in English Literature in 2018 at state University of Makassar was the subject of this investigation. To characterize a phenomenon, the study used a descriptive qualitative method. To figure out why they used code mixing, the researcher merged Muysken's theory, which categorized three types of code mixing, with Hoffman's theory. Based on the utterances, the purpose of this study is to determine what type of code mixing is used and why. According to the research, the three most popular methods of code mixing used in WhatsApp Academic groups talks are word insertion, phrase insertion, and alternation. They used code mixing for four reasons: talking about specific issues, repetition for clarification, the goal of clarifying speech content for interlocutors, and they couldn't locate the suitable phrase in any language other than their own.